Podcast Berseri Sebagai Media Pembelajaran Bahasa Indonesia Untuk Keperluan Akademik Era Digital - Alifiah Nurachmana; Petrus Poerwadi; Lazarus Linarto; Linggua Sanjaya Usop; Paul Diman (FKIP, Universitas Palangka Raya, 2023)
The use of technological advances has given rise to new media for all fields, including the use of technology in the field of education. This allows the development of alternative learning media that can help the process of teaching courses in higher education. A teacher is required to be able to adapt to technology and use it as a creative and innovative learning tool or medium. The use of digital-based learning media allows students to study these materials anywhere and at any time.Serial podcasts as a medium for learning Indonesian for academic purposes in the digital era are a development product carried out by a team of digital-based media and learning resource developers. This podcast consists of eight episodes containing material related to learning Indonesian. The development of this learning media aims to describe and present eight podcasts with different material for each episode. Determining the type of media development product has been considered from the important elements and characteristics of selecting learning media that suit student needs. The development of this learning media uses a 4 D model which has four stages, namely (1) define, (2) design, (3) develop; and (4) disseminete or distribution. The results of this learning media development product include the following materials: (1) Indonesian for Academic Purposes in the Digital Era, (2) Spelling in Indonesian, (3) Sentences in Indonesian, (4) Topic 4: Paragraphs in Indonesian , (5) Utilization of Digital Technology to Improve Indonesian Language Skills, (6) Indonesian in Academic Communication, (7) Indonesian in Scientific Research and Publications, and; (8) Challenges and Opportunities of Indonesian in the Digital Era which have been published on the ”Siniar Enggang” YouTube account (https://www.youtube.com/@SiniarEnggang).